Estudos da aplicação do corante azul de metileno em terapia fotodinâmica - Peloi, Lilian Somenci (2007)
The Photodynamic Therapy (PDT) is a medical modality that utilizes a combination of a photosensitizer compound, visible light and oxygen. Its largest application is in the treatment of cancer, however, this technical is being diffused far handling other illnesses including microbial infections. Despite of the wide applicability of the TFD, two factors difficult its dissemination: the high cost of the medicines and the light source. The option of dyes as the photodynamic agents is interesting due to the lower cost and possibilities, of application being an example the Methylene Blue (MB). This dye absorbs in the red region of the visible absorption spectra and produces high level of singlet oxygen. Beyond that, it is already utilized in the medical area, for example, to treat metahemoglobinemia, and has been considered a medication for PDT. In the case of equipment, the replacement of the LASER by LED units as light source should be investigated. In that way the MB was investigated in association with LED light as an alternative for PDT. It was investigated the photoactivity of MB in cultures of microorganisms and Artemia salina and in the handling of the American Tegumentar Leishmaniosis. The Methylene Blue has a maximum absorption in 663 nm (inside the phototherapeutic windows for PDT); suffers almost no photobleaching reaction and exhibits a good value of photodynamic activity (PA). This last parameter was calculated considering the fact of the LED be a nonmonocromatic light source, leading us to modify the equation traditionally employed for LASER systems in the calculations of PA. The apparatus of LED system developed was highly convenient for the proposed application with the MB dye. The photoactivity of MB/LED was investigated using the bacteria Staphylococcus aureus and Escherichia coli, and the fungus Candida albicans. A tiny microcrustaceous Artemia salina was also tested. All the microorganisms studied mesented inhibitory growth activity and killing effect in presence of MB (in the dark), being this action intensified with the LED light irradiation. The intensity of effect using MB/LED was similar for ali of the microorganisms. Equally with Artemia salina the percentage of death was higher in the irradiated samples. To American Tegumentar Leishmaniosis (LTA) is one of the parasitic disease of largest incidence in the world and in the conventional treatment employ some costly medicines which show severe colateral effects. The investigation for LTA through LED in association with MB, was carried out in vitro, in attempt promastigotes and amastigotes forms of Leishmania (Viannia) braziliensis and, in vivo with Leishmania (Leishmania) amazonensis infected in hamsters. The results in vitro show that the combination of MB and light inhibited the growth of forms promastigotes in culture and reduced the capacity of infection of the promastigotes in macrofhages. The results in vivo show that the system MB/LED reduced the lesion of the infected paw and the parasitic load in the hamsters. The good results showed in the treatment applied against microorganisms and leishmaniosis, in vitro and in vivo with the MB/LED, pointed out that this therapy is very interesting and can be a future alternative in the clinical handling of patients.